Acquired Brain Injury in the Context of Family Violence: A Systematic Scoping Review of Incidence, Prevalence, and Contributing Factors. (January 2021) - Ayton, Darshini; Pritchard, Elizabeth; Tsindos, Tess
Brain injury is often a precursor to, or result of, family violence. Yet there is little research identifying the connection of these two phenomena. The health cost (personal or societal) of brain injury within the family violence context is difficult to ascertain. Family violence can lead to lifelong psychological or physical scars and even death. A systematic review was conducted over three databases using Medical Subject Heading terms to investigate incidence, prevalence, and contributing factors of brain injury within a family violence context. Inclusion criteria were primary studies, any person who experienced traumatic brain injury in a familial context. Seven hundred and seven studies of varied designs were initially identified with 43 meeting inclusion criteria. Data were extracted and a deductive narrative synthesis was performed. The accuracy and generalizability of incidence and prevalence statistics was hindered by underreporting of family violence and the specificity of some of the population groups (e.g., female inmates). The factors contributing to brain injury within the family violence context had multifactorial causation and varied greatly across the populations studied. Five social determinants of health were identified: biological, behavioral, structural, social, and environmental. These factors included age and gender of parent/baby, crying as an antecedent of family violence, previous exposure to abuse as a child, hostile living environments, previous trauma, financial pressures, employment status, housing availability, and exposure to natural disasters. Future investigation into the nexus between brain injury and family violence is required; however, this is complicated due to global inconsistency of definitions, assessment tools, and research methods used.